Healthy lifestyle promotion and its effect on general practitioners at National Oncology Institute March – April 2021: Efectos de la promoción de estilo de vida saludable en los médicos generales del Instituto Oncológico Nacional marzo-abril 2021 - Hernández Núñez, Irma A. (2021)
Introduction: The medical population is considered a representation of integral health. Its work characteristics predispose each member to be complicit in an unconscious practice and promotion of an unhealthy lifestyle. The aim of this work was to describe the effects on lifestyle of an educational intervention in general practitioners in an active work environment. Methods: This study included 18 general practitioners working at the “Instituto Oncológico Nacional de Panamá”. It consisted of 10 virtual educational sessions delivered by trained professionals for 2 months. Results: Positive changes and improvement in all measured variables were reported, including increased frequency of exercise sessions, increased duration of each session, increased consumption of fruits, vegetables, legumes and seeds, increased hours of sleep, improvement in the perceived stress scale score and a decrease in the consumption of foods with low nutritional quality. Discussion: Truly little evidence exists regarding lifestyle promotion educational interventions aimed at health professionals. This population has a high predisposition to form a poor-quality lifestyle since the work environment in which the physician develops exposes him/her to adverse situations such as rotating schedules and long working hours with sleep deprivation. Conclusions: This practical and low-cost educational intervention achieved improvements in the lifestyle of physicians. For this reason, we recommend the replication of similar interventions and their documentation.